Motivações de usuário de substâncias psicoativas e a atenção à saúde - Siqueira, Daiana Foggiato de (2015)
The use of psychoactive substances represents a worrying health problem due to the increasing number of users of these substances, together with the social grievances arising from that consumption. This research aims to understand the reasons given by users of psychoactive substances seeking treatment at a Psychosocial Care Center Alcohol and Drugs. This is a research based on the Social Phenomenology of Alfred Schütz, made in a Psychosocial Care Center Alcohol and drugs, located in the central-western region of the state of Rio Grande do Sul, Brazil. Participants in this study were users of psychoactive substances, aged 31to 58 years old who were undergoing treatment at the Psychosocial Care Center Alcohol and Drugs. The data production occurred in the period from March to June 2014, through the phenomenological interview recorded, which was ended when there were sufficient meanings. The comprehensive interpretation of the speeches was developed, in which the steps mentioned by an author of the nursing field that has been studying the Social Phenomenology of Alfred Schütz were used. The ethical aspects were respected according to the Resolution 466 of December 12th, 2012 by the National Health Council. In the comprehensive analysis of users' characteristic action of psychoactive substances seeking treatment, were unveiled concrete categories of lived of the reasons why and reasons for. Regarding the reasons why, two categories emerged: grievances in health; and social relationships. As to the reasons for, three categories emerged: intent to break the custom of the use of psychoactive substances; bearing in mind the (re)construction of their family relationships; expectation of getting back to society. It is hoped that this research provides subsidies for health professionals to review their practices in order to stimulate the strengthening of psychosocial care service network that emphasizes rehabilitation and social reintegration of the user. Thus, it is intended to contribute to the integration of the psychoactive substances user in the cultural milieu, articulated to the mental health network.